The Extreme Activity in Comet Hale–Bopp (C/1995 O1): Investigations of Extensive Narrowband Photoelectric Photometry - David G. Schleicher; Peter V. Birch; Tony L. Farnham; Allison N. Bair (The Planetary Science Journal)
Conventional narrowband photoelectric photometry of Comet Hale–Bopp (1995 O1) was obtained on 99 nights from mid-1995 to early-2000, yielding gas and dust production rates over an unprecedented range of time and distance. The appearance of Hale–Bopp (H-B) presented a prime opportunity for active comet studies, and its inherent brightness and orbital geometry allowed the characterization of its long-term activity. Throughout the apparition, H-B released, by far, more gas and dust than any other comet ever measured. As a very high dust-to-gas ratio object, dust production was successfully measured throughout the apparition, with the dust consistently slightly red in color. All five gas species including OH and NH were detected just inside of 5 au inbound, while C _2 and C _3 were detected to just past 5 au outbound, and CN was followed until nearly 7.7 au. Heliocentric distance dependencies ranged between −1.2 and −2.7 in log–log space, with the extremes magnified by the large extrapolations in Haser model parameters at large distances. H-B’s enormous size and associated extremely high outgassing resulted in a much larger collisional zone, which in turn yielded outflow velocities more than 2× higher than ever previously measured at comparable distances. Even so, volatile composition remained within the “typical” classification, consistent with most Oort Cloud comets, and water production follows the expected curve based on a standard water vaporization model. However, seasonal effects provided evidence for inhomogeneities among the major source regions on the surface of the nucleus. Preliminary modeling of the nucleus and coma successfully matches this seasonal behavior.